EXPLORING BIOCHAR AS A SUSTAINABLE STRATEGY FOR SUPPRESSING MACROPHOMINA PHASEOLINA CAUSING ROOT AND STEM ROT OF SESAME (Journal of Plant Disease Sciences, 2026)
Sesame (Sesamum indicum L.) is an important oilseed crop widely cultivated in tropical and subtropical regions. However, its productivity is severely affected by root and stem rot caused by Macrophomina phaseolina, a soil-borne pathogen that survives in soil through persistent microsclerotia and causes significant yield losses, particularly under high-temperature and moisture-stress conditions. The present study was conducted to evaluate the efficacy of eucalyptus wood biochar, applied alone and in combination with beneficial bioagents, for the management of root and stem rot of sesame under controlled conditions. The experiment was laid out in a Completely Randomized Design (CRD) with seven treatments and three replications. Biochar was applied at different concentrations (5, 10, and 30 g kg⁻¹ soil) either alone or in combination with Trichoderma viride, Pseudomonas fluorescens, Bacillus subtilis, and Jawahar Mycorrhiza. Observations on seed germination, shoot length, root length, and disease incidence were recorded at 30, 45, and 60 days after sowing (DAS). Among all treatments, biochar at 5 g kg⁻¹ soil combined with T. viride proved to be the most effective, recording 88.77% disease reduction over the untreated control at 60 DAS, along with the highest germination (66.60%) and improved plant growth. In contrast, the higher biochar concentration (30 g kg⁻¹ soil) was comparatively less effective, indicating a dose-dependent response. Overall, the integration of eucalyptus wood biochar with beneficial bioagents effectively suppressed M. phaseolina and enhanced sesame growth, suggesting its potential as an eco-friendly strategy for managing root and stem rot of sesame.
Keywords: Biochar; Macrophomina phaseolina; Root and stem rot; Sesame